Responsibilising Managers and Clinicians, Neglecting System Health? What Kind of Healthcare Leadership Development Do We Want? Comment on "Leadership and Leadership Development in Healthcare Settings - A Simplistic Solution to Complex Problems?" - Graham P. Martin (Kerman University of Medical Sciences, 2015)
Responding to Ruth McDonald's editorial on the rise of leadership and leadership development programmes in healthcare, this paper offers three arguments. Firstly, care is needed in evaluating impact of leadership development, since achievement of organisational goals is not necessarily an appropriate measure of good leadership. Secondly, the proliferation of styles of leadership might be understood in part as a means of retaining control over public services while distributing responsibility for their success and failure. Thirdly, it makes a plea for the continued utility of good administrative skills for clinicians and managers, which are likely to become all-the-more important given recent developments in healthcare policy and governance.